Incidence of short-term community hospital stays and clinical profiles of patients: the Finnish Community Hospital Cohort Study - Henna Saari; Eija Lönnroos; Hannu Kautiainen; Simo Kokko; Olli-Pekka Ryynänen; Pekka Mäntyselkä (Taylor & Francis Group, 2024)
AbstractObjective A community hospital system covers the entire population of Finland. Yet there is little research on the system beyond routine statistics. More knowledge is needed on the incidence of hospital stays and patient profiles. We investigated the incidence of short-term community hospital stays and the features of care and patients.Design Prospective observational study.Setting Community hospitals in the catchment area of Kuopio University Hospital in Finland.Subjects Short-term (up to one month) community hospital stays of adult residents.Main outcome measures The outcome was the incidence rate of short-term community hospital stays according to age, sex and the first underlying diagnoses.Results A number of 13,482 short-term community hospital stays were analyzed. The patients' mean age was 77 years. The incidence rate of short-term hospital stays was 28.6 stays per 1000 person-years among residents aged <75 years and 419.0 among residents aged ≥75 years. In men aged <75 years, the hospital stay incidence was about 40% higher than in women of the same age but in residents aged ≥75 years incidences did not differ between sexes. The most common diagnostic categories were vascular and respiratory diseases, injuries and mental illnesses.Conclusions The incidence rate of short-term community hospital stays increased sharply with age and was highest among women aged ≥75 years. Care was required for acute and chronic conditions common in older adults.Implications Community hospitals have a substantial role in hospital care of older adults.